Эволюция ПЛИС серии Spartan на архитектуре FPGA - Красношапка, Т. Ю.; Заворотна, М. Г. (ХНУРЕ, 2019)
The evolution of the FPGA chips of the Spartan series is considered in the paper. Describes the relevance of the chip at the moment, as well as the distinctive features of each device. A comparative characteristic shown in graphical form. FPGA Spartan series is a family of programmable chips with built-in RAM by Xilinx. They are widespread. The FPGA Spartan series is the affordable prices of the XC400 series. The FPGA community in two ways. The first direction allows the implementation of efficient and technically complex architectures.
Keywords: ПЛІС; FPGA; Xilinx; Spartan